Piston Analysis with Different Material Subjected to Thermal Analysis - Abu Bakar, Muhammad Amirul Firdaus; Wan Abdul Rahman, Wan Mohd Wardi (Progress in Engineering Application and Technology, 2021)
The piston operates for long periods in high temperatures and high load conditions as the main heating component of the engine. The piston has large heating surface and poor heat dissipation characteristics, rendering the thermal load a big issue. This thesis is a numerical method for calculating thermal stress caused only by uneven temperature distribution using thermal mechanical FEM (Finite Element Method). The main focus of this work is the study of thermal behavior by means of the application of commercial ANSYS code on aluminium alloys, grey cast iron and Metal Matrix Composite (MMC) piston surfaces of functionally graded materials. The analysis helps to lower tension at the top of the piston (head / crown piston and skirt / sleeve). The tension is determined by the analysis. SolidWorks software will develop a piston structural model with computer-aided design. The finite element analysis also takes place using the ANSYS program for computer aided simulation.